2004
DOI: 10.1182/blood-2004-05-1850
|View full text |Cite
|
Sign up to set email alerts
|

L-Selectinhi but not the L-selectinlo CD4+25+ T-regulatory cells are potent inhibitors of GVHD and BM graft rejection

Abstract: Graft-versus-host disease (GVHD) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
247
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(273 citation statements)
references
References 24 publications
22
247
2
2
Order By: Relevance
“…To test this premise, we established an acute model of graft-versus-host disease (aGVHD) using irradiated major histocompatibility complex (MHC) haplotype H2 d animals that received allogeneic T cells (MHC haplotype H2 b ) in concert with CD62L low Tregs; alternatively, CD62L low Tregs were transduced with a nondegradative form of KLF2 (16,28) before cotransfer. Consistent with previous reports (29,30), CD62L low Tregs were unable to prevent aGVHD (Fig. 5A) because of inefficient entry into SLOs.…”
Section: Increased Klf2 Expression Within the Treg Compartment Augmentssupporting
confidence: 81%
“…To test this premise, we established an acute model of graft-versus-host disease (aGVHD) using irradiated major histocompatibility complex (MHC) haplotype H2 d animals that received allogeneic T cells (MHC haplotype H2 b ) in concert with CD62L low Tregs; alternatively, CD62L low Tregs were transduced with a nondegradative form of KLF2 (16,28) before cotransfer. Consistent with previous reports (29,30), CD62L low Tregs were unable to prevent aGVHD (Fig. 5A) because of inefficient entry into SLOs.…”
Section: Increased Klf2 Expression Within the Treg Compartment Augmentssupporting
confidence: 81%
“…Whereas CCR7-deficient naive-like Treg fail to recirculate through LN, resulting in an almost complete abolishment of their ability to inhibit the proliferation of naive T cells at this site, effector/memory-like Treg from CCR7 -/-mice display an increased accumulation in inflamed sites, which was accompanied by an enhanced suppression of the inflammatory reaction. CCR7 expression was predominantly observed on naive-like Treg [3,5,6,11,[31][32][33][34] and CCR7-expressing CD62L high CD25 + CD4 + Treg were found to be very efficient in preventing the development of autoimmunity [5] or in suppressing graft-versus-host disease [35,36]. It was suggested that Treg recirculation through LN mediated by CCR7 and CD62L is a prerequisite to suppress priming of autoreactive effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] For example, CD8 þ TCR À -facilitating cells, derived from BM, induced Treg genes (including Foxp3) 28 days after transplantation. 48 This was observed at the time of full donor engraftment, suggesting that these putative CD4 þ CD25 þ Treg cells were of donor origin.…”
Section: Discussionmentioning
confidence: 99%